Is there a taxonomic crisis? - Bradford-Grieve, Janet (New Zealand Science Review, 2016)
Concern has been expressed around the world concerning the ‘taxonomic crisis’: that is, although biodiversity is being lost at an ever-increasing pace, species discovery and description (taxonomy) is facing a crisis. Recently, a number of papers have been published that suggest there is not a taxonomic crisis, based on electronic databases that contain uncritically recorded species synonyms and that do not make it clear who the taxonomist is on multi-authored papers. Claims that there have never been more taxonomists are likely to be incorrect especially if they are made by non-taxonomists not intimately familiar with the limitations of each electronic dataset and the taxonomic enterprise. In response to concerns in New Zealand about the precarious position of collections (scattered across several types of institution with separate funding sources) and associated taxonomic expertise, the Royal Society of New Zealand (RSNZ) convened a panel to look into the situation in New Zealand resulting in a report published in 2015. The panel confirmed that collections and taxonomy play an important role in a wide range of national activities (economic, biosecurity, human health, conservation, sustainable use, etc.). The RSNZ report noted the lack of strategic connection between science funders and priority setters and a lack of alignment between the funding of collections infrastructure and the delivery of services. The taxonomic workforce in New Zealand is characterised as ageing, male-dominated, and with very low numbers in the 19-30 age group. This workforce is mostly not doing taxonomic research (77% were funded to spend less than 25% on research and 59% could spend less than 10% on research) resulting in a zero to low published output for the majority. This suggests that qualified researchers are underused in New Zealand and risk not being up-to-date and in danger of eroding their capability. Compared with Canada in 2009 and Australia in 2003, New Zealand has the lowest proportion of researchers in the 20-40 age bracket. Compared with Canada, a very small proportion (4%) of researchers in museums can spend more than 50% of their time on taxonomic research in New Zealand (58% in Canada). A solution needs to be found to the problem created by diffuse responsibilities for taxonomic collections infrastructure and lack of strategic connection between science funders and priority setters. This solution should include the creation of a national co-ordination mechanism.